Investigação da interface metal-porcelana da liga Ni-Cr-Mo soldada a LASER - Ernesto, Vívian Aparecida Ricardo Teixeira [UNESP]; Guastaldi, Antonio Carlos [UNESP] (My University, 2008)
The interface formed between the metal and the porcelain of a LASER welded Ni-Cr-Mo alloy was studied. The characterization was carried out through optical microscopy, scanning electron microscopy, X-ray dispersive spectroscopy-EDS and mechanical testing by three-point flexion test-TPF, in the region LASER welded with and without the porcelain. The porcelain adhesion with the alloy alone is possible after the oxidation of the metallic surface and subsequent application of an adhesive called opaco. The applied porcelain, on the base metal and fusion zone presented some distinct behaviors. After the TPF test the base metal presented fractures while that in the fusion zone was completely gone. One noticed that the region submitted to the LASER welding showed less porcelain adhesion than the region of the base metal due to the microestructural refinement of the fusion zone. These results can be evidenced by the EDS of the studied regions. The TPF had demonstrated that the Ni-Cr-Mo alloy submitted to the LASER welding, undergone significant alterations in its mechanical properties after the application of the porcelain.
Research of the metal-pocelain interface of the LASER welded Ni-Cr-Mo alloy
Keywords: Laser beam welding; Metalo-ceramic prostheses; Ni-Cr-Mo alloy